Simulation Analysis of the Dynamic Performance of Multi Tooth Meshing of Filtering Reducer based on ANSYS- LS / DYNA - Lei Xiaochun; Yang Rongsong; Zhu Bingfeng; Liu Qiang; Chen Zhiliang (Jixie chuandong)
The filtering reducer structure principle and multi tooth elastic meshing effect are introduced,with the help of explicit dynamics software ANSYS / LS- DYNA,the three- dimensional nonlinear finite element contact analysis model is established,the dynamic meshing simulation of gear transmission mechanism under a certain speed and different load torque is carried out,the tooth surface contact stress,tooth root bending stress distribution and the rules of contact force changes under the condition of multi tooth contact with time are obtained,a theoretical basis for further filter reducer gear strength analysis and fatigue life calculation is provided by this method.